THE MORAL DIMENSION REFLECTED IN THE SONGS TOMORROW AND WHALIEN 52 BY BTS - Maulida, Sri Dewi Zahra Atira; Nirwan, Nirwan; Lestari, Noviana (Universitas Putera Batam, 2024)
Music is an important component of human existence. It has the power to change the listener's mood and evoke emotions. This is a reflection of human love for the beauty of rhythm. To fully appreciate the beauty of music, the lyrics and rhythm must be in harmony with the listener's emotions. This research analyzes the moral meaning of BTS's